PERLINDUNGAN KEKERASAN TERHADAP PENGAMEN JALANAN STUDI KASUS: PADA ANAK SEBAGAI PENGAMEN JALANAN DI PANTAI PURUS - Irza Ardinazul Aqiah; Nur Hazizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of street children working as buskers in the Pantai Purus tourist area, Padang City, is a crucial issue related to violations of children's rights and the risk of violence. This research aims to evaluate the forms of violence experienced by street busker children and the protection efforts carried out by related parties. The research method used is qualitative with a case study approach. Data were collected through observation, in-depth interviews, and documentation. The research results show that child street buskers are vulnerable to physical, verbal violence, and economic exploitation from both the street environment and family economic pressure. Protection efforts carried out include intervention from the Social Service through coaching and rehabilitation programs, but are still constrained by family resistance and social environment factors. In conclusion, more intensive collaboration is needed between the government, community and families to guarantee children's safety and education rights.